In situ cytokine gene expression in early stage of virulent Newcastle disease in chickens. Issue 1 (January 2022) - Brown, Corrie; Zhang, Jian; Pantin-Jackwood, Mary; Dimitrov, Kiril; Ferreira, Helena Lage; Suarez, David
Selected lymphoid and reproductive tissues were examined from groups of 3-week-old chickens and 62-week-old hens that were inoculated choanally and conjunctivally with 10 6 EID50 of a virulent Newcastle disease virus (NDV) isolate from the California 2018–2020 outbreak, and euthanized at 1, 2, and 3 days postinfection. In the 3-week-old chickens, immunohistochemistry for NDV and for T and B cell lymphocytes, as well as in situ hybridization for IL-1β, IL-6, IFN-γ, and TNF-α revealed extensive expression of IL-1β and IL-6 in lymphoid tissues, often coinciding with NDV antigen. IFN-γ was only expressed infrequently in the same lymphoid tissues, and TNF-α was rarely expressed. T-cell populations initially expanded but by day 3 their numbers were below control levels. B cells underwent a similar expansion but remained elevated in some tissues, notably spleen, cecal tonsils, and cloacal bursa. Cytokine expression in the 62-week-old hens was overall lower than in the 3-week-old birds, and there was more prolonged infiltration of both T and B cells in the older birds. The strong pro-inflammatory cytokine response in young chickens is proposed as the reason for more severe disease.